The Institutionalization of Remuneration (A Case Study at the University X) - Kharisma Yuanita Mahanani; Bambang Hariadi; Roekhudin Roekhudin (Universitas Negeri Malang, 2020)
This study aims to understand the process of institutionalization that occurred in the University X (UX) with their remuneration policy, starting from the idea of remuneration, remuneration discourse preparation, implementation and dissemination of remuneration. This is a qualitative research with case study approach to gain an understanding of the process of remuneration institutionalization at the UX. The results of this study indicate that the process of institutionalization of remuneration at the UX was related to external and internal factors of the organization. Determination of the remuneration regulation is the external pressure which must be accepted by the UX because it has implemented public service institution (BLU) financial management system. The idea of improving the quality of public services which was followed by the remuneration policy discourse and its application were not running well for the UX should face internal pressure from lecturers. In addition, education staffs who still do not have the application performance measurement weakens the process of institutionalization.